1988
DOI: 10.1083/jcb.106.3.979
|View full text |Cite
|
Sign up to set email alerts
|

Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken embryo osteoblasts.

Abstract: Abstract. A newly defined chick calvariae osteoblast culture system that undergoes a temporal sequence of differentiation of the osteoblast phenotype with subsequent mineralization (Gerstenfeld, L. C., S. Chipman, J. Glowacki, and J. B. Lian. 1987. Dev. Biol. 122:49-60) has been examined for the regulation of collagen synthesis, ultrastructural organization of collagen fibrils, and extracellular matrix mineralization. Collagen gene expression, protein synthesis, processing, and accumulation were studied in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 59 publications
9
98
0
2
Order By: Relevance
“…This observation, suggests that these polymers may increase the deposition of insoluble collagen in wounds treated with DBC or PCL. 32,33 Histological studies show similar responses of the tissue to implantation of both PCL and DBC. The implantation of biomaterials ( Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This observation, suggests that these polymers may increase the deposition of insoluble collagen in wounds treated with DBC or PCL. 32,33 Histological studies show similar responses of the tissue to implantation of both PCL and DBC. The implantation of biomaterials ( Fig.…”
Section: Discussionmentioning
confidence: 76%
“…The solubility of collagen in neutral salt solutions reflects its degree of maturation, cross-linking or catabolism. 32 Collagen fibre maturation occurs when intermolecular covalent bond formation causes progressive loss of solubility of the molecule. In both the DBC and PCL groups, the soluble collagen level was lower in the second week of healing and persisted at the lower level for the duration of the experiment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The nodules stain for alkaline phosphatase [4,42], and are the regions where bone extracellular matrix proteins are deposited [36] and mineralization occurs. Previous studies have shown that the mineralized nodules resemble woven bone that is produced in vivo [4,8,13,20,42]. On implant disks, phalloidin labeling of the actin-based cytoskeleton showed a confluent layer of cells with multilayering creating nodules (Fig.…”
Section: Expression Of Mrna Levels For Hone Matrix Proteins and Ininementioning
confidence: 99%
“…Presumably, it seems that the ability of the keratin fibers have the capacity to form the seeds to produce feather like HA, Ca/P will tend to approach 1.67 with crystal growth (Elliott, 1969;Hauschka et al , 1975;Moreno et al , 1977). Gerstenfeld et al (1988) studied a relationship between certain protains and the functional development of matrix mineralization (Dimuzio et al, 1978;Kallenbach, 1986;Termine et al , 1981). In general, there are two different posibilities of the process of mineralization; one is the mineralization induced by matrix vesicle as an initiator (Bernard et al, 1981), the other directly relates with mineral deposition among the keratin fibres.…”
Section: Discussionmentioning
confidence: 99%